COMPETITIVE AGGRESSIVENESS AND ANGER SCALE: VALIDITY AND RELIABILITY STUDY - Bülent Gürbüz; Sercan Kural; Oğuz Özbek (ümit doğan üstün, 2019)
This study aimed to test "Competitive Aggressiveness and Anger Scale"s reliability and validity to measure Turkish athletes' aggressiveness and anger. Study participants were 53 professionals (21.5 %) and 193 (78.5 %) amateur football players. They ranged in age from 17 to 37 years old (Mage= 21.60±3.97). The participants answered the "Competitive Aggressiveness and Anger Scale" (CAAS) which was developed by Maxwell and Moores (2007). Original version of the scale constitutes of two subscales which are named as aggressiveness (6 items) and anger (6 items). After testing the basic assumptions of statistical tests, Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were used to test the factor structure of the scale. Cronbach's Alphas were calculated for the subscales to test their internal consistencies. EFA results illustrated that adapted scale consists of two subscales. CFA results revealed that Turkish version of the scale consists of two subscales and totally 12 items and these results were similar to the original version of the scale. The item factor loadings for the overall scale range between .41 and .83. When the fit indexes were examined, the fit indexes of the scale were χ2/df= 2.69, GFI= .91, AGFI=.87, CFI=.91, IFI=.91, SRMR=.07, RMSEA=.08. The goodness of fit indexes indicated that these indexes of scale were in acceptable ranges. For the total scale and the subscales, the Cronbach's Alpha reliability coefficients were measured as .79, .79 and .83 respectively. In conclusion, the results revealed that the Turkish adaptation of "Competitive Aggressiveness and Anger Scale" can be used as a valid and reliable measurement tool to evaluate the athlete's competitive aggressiveness and anger.